Trends in computational social choice - Endriss, Ulle [Ed.] (Ahemdabad ILLC, 2017)
Computational social choice is concerned with the design and analysis of methods for collective decision making. It is a research area that is located at the interface of Computer Science and Economics. This volume reports on a number of recent research trends in computational social choice. It has three parts. The first part presents novel scenarios in which methods for collective decision making are required. The second part introduces novel techniques for the analysis of such methods. The third part, finally, discusses a range of innovative applications enabled by recent research in computational social choice
Keywords: Computer science